Informasi peramalan banjir menggunakan data hujan dari satelit - Pian Sopian Amsori; Tasya Asyantina; Radhika Radhika (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2017)
Flood disaster is one of the natural disasters that always occur in various regions in Indonesia. One of the causes is the high rainfall that often occurs in all regions in Indonesia. In order to minimize the losses caused by the disaster, it is necessary to make information system of flood forecasting that is disseminated to relevant stakeholders in every area of water resources management which is limited by river area. This paper presents a flood early warning information system that informs the potential for floods for up to two days ahead, using inputs in the form of static data (socio-economic vulnerability map, flood hazard map and land slope map) and dynamic data (TRMM rainfall and forecasting data). The method used is to overlay static and dynamic data on FEWS (Flood Early Warning System) software and with certain limitations in determining the potential of flood generating output in the form of map of potential flood information in every region in Indonesia for today condition up to two days ahead. The objective of a flood early warning information system is to present flood early warning information in Indonesian Territory and the result is expected to be used by the stakeholders in facing the flood-related threat in their area.